2011
DOI: 10.1007/s13258-010-0132-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of TMC1 gene in the Korean patients with nonsyndromic hearing loss

Abstract: Hereditary nonsyndromic hearing loss (NSHL) is a highly heterogeneous disorder in humans. Mutations of the transmembrane channel-like (TMC1) gene have been identified as the genetic cause for both autosomal recessive (DFNB7/11) and autosomal dominant (DFNA36) nonsyndromic hearing loss. To evaluate the spectrum and frequency of mutation(s) caused by TMC1 gene in the Korean population, we have performed sequencing analysis of the PCR products amplified from genomic DNA of each proband in 193 unrelated families s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Kalay et al (2005) investigated four novel TMC1 (DFNB7/DFNB11) mutations in Turkish patients with congenital autosomal recessive NSHL (ARNSHL), and they indicated that TMC1 mutations account for at least 6% (4/65) of ARNSHL cases in GJB2 -negative Turkish families from the northeast and east of Turkey; however, in our study, mutation in exons 7 and 13 of TMC1 gene was not observed ( 14 ). In another study in Sudan, it was shown that TMC1 mutations contribute to deafness; this confirmed and extended previous reports on the role of TMC1 in recessive non-syndromic deafness ( 20 , 21 ). Meanwhile, in the present study on the Iranian population, no significant relation between exon 7 and 13 mutations of the TMC1 gene were observed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Kalay et al (2005) investigated four novel TMC1 (DFNB7/DFNB11) mutations in Turkish patients with congenital autosomal recessive NSHL (ARNSHL), and they indicated that TMC1 mutations account for at least 6% (4/65) of ARNSHL cases in GJB2 -negative Turkish families from the northeast and east of Turkey; however, in our study, mutation in exons 7 and 13 of TMC1 gene was not observed ( 14 ). In another study in Sudan, it was shown that TMC1 mutations contribute to deafness; this confirmed and extended previous reports on the role of TMC1 in recessive non-syndromic deafness ( 20 , 21 ). Meanwhile, in the present study on the Iranian population, no significant relation between exon 7 and 13 mutations of the TMC1 gene were observed.…”
Section: Discussionsupporting
confidence: 86%
“…The strength of this study was the number of samples, as 890 blood samples were provided; however, due to a lack of financial resources, we chose two exons of this gene. Via the molecular analysis of the TMC1 gene in Korean patients, one study showed that this gene was not the cause of NSHL in the Korean population ( 20 ). In our study, as in the research in Korea, a relation between the TMC1 gene and NSHL in the Iranian population was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the U-TOP™ HL Genotyping Kit Ver2 is not necessarily limited to ANSD. Indeed, the development of this new kit was based on the recent identification of several prevalent variants exerting a potential hotspot/founder effect or manifest specific auditory phenotypes in the Korean hearing-impaired population [ 15 , 16 , 17 , 18 , 19 , 20 ]. This new kit was designed to detect as many recurring and important deafness-causing variants as possible in conjunction with the previous version, U-TOP™ HL Genotyping Kit Ver1.…”
Section: Discussionmentioning
confidence: 99%
“…This issue implicates some major variants of other deafness genes as well. Indeed, several prevalent variants that exert a potential hotspot/founder effect or manifest specific auditory phenotypes have been recently identified in the Korean population with varying degrees of SNHL [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%